Implementation of Freedom in Islamic Economics - Karmila, Yusri; Wahab, Abdul; Sabbar, Sabbar; Bado, Basri (Journal International Economic Sharia, 2024)
Freedom in liberal and Islamic economic systems is interesting to study. This research aims to explore the implementation of freedom in Islamic economics. This research describes this phenomenon as it exists according to the point of view or approach used. Documentation techniques are used to collect data in the form of the Al-Qur'an, books and articles referenced from online, print and internet journals. Data collection is carried out to obtain materials that are relevant, accurate and reliable. This research is qualitative research in which the research procedures produce descriptive data in both written and verbal form from the object under study. The data that has been collected is then analyzed and concluded deductively, namely drawing conclusions from general statements to specific statements. It is concluded that the implementation of the concept of freedom in the Islamic economic system can be explained in two perspectives, namely: the theological perspective and the ushul fiqh perspective. Meanwhile, the implementation of freedom in the Islamic economic system is freedom in morals, namely morals in consumption, morals in production, and morals in distribution. Even though there is freedom in the Islamic economy, there are still limitations to Islamic law that must be obeyed.